Is increasing the dose of Entecavir effective in partial virological responders? - Erturk A; Adnan Akdogan R; Parlak E; Cure E; Cumhur Cure M; Ozturk C (Dove Medical Press, 2014)
Ayse Erturk,1 Remzi Adnan Akdogan,2 Emine Parlak,3 Erkan Cure,2 Medine Cumhur Cure,4 Cinar Ozturk1 1Department of Infectious Diseases, 2Department of Gastroenterology, School of Medicine, Recep Tayyip Erdoğan University, Rize, Turkey; 3Department of Infectious Diseases, School of Medicine, Ataturk University, Erzurum, Turkey; 4Department of Biochemistry, School of Medicine, Recep Tayyip Erdoğan University, Rize, Turkey Objective: To analyze the effect of increasing Entecavir (ETV) dosage in patients with chronic hepatitis B (CHB) who partially responded to ETV after 1 year. Methods: Twenty-three hepatitis B e antigen (HBeAg)-positive and 36 HBeAg-negative patients with CHB were treated with ETV 0.5 mg daily. After 1 year of the treatment, those with detectable hepatitis B virus (HBV-DNA) were randomized to either ETV 0.5 mg or 1 mg daily. The resistance to ETV was excluded. Both groups received ETV for 3 years. The groups were compared in aspects of undetectable DNA. Results: Group 1 was given 0.5 mg ETV and included 32 patients (20 HBeAg-negative and 12 HBeAg-positive). Group 2 was given 1 mg ETV and consisted of 27 patients (16 HBeAg-negative and eleven HBeAg-positive). Group 2 had more effective suppression of HBV-DNA while both groups had comparable rates of HBeAg loss (58% and 63% for group 1 and group 2, respectively) and alanine transaminase (ALT) normalization at the end of 4 years. Conclusion: Increasing ETV dose from 0.5 mg to 1 mg after 1 year of ETV treatment may provide an effective suppression of viral replication. Keywords: chronic hepatitis B, treatment, entecavir, treatment, patient monitoring